Pengembangan Sistem Informasi Manajemen Sekolah Berbasis Web untuk Meningkatkan Efisiensi Administrasi Pendidikan - Eka Indah Wahyuni; Fatimah Muthmainnah; Bintang Permana; Tulas Novalima (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
This research aims to develop a web-based school management information system that can improve the efficiency of education administration. In today's digital era, many schools face challenges in effective data and information management. This research uses a Systematic Literature Review (SLR) approach to identify and analyze relevant literature related to the development of web-based school management information systems. The results showed that the development of a web-based school management information system is generally able to improve the efficiency and effectiveness of education administration management, starting from data processing of students, teachers, finances, to reporting. The system supports transparency, speed of access and accuracy of information within the school environment. Although the results show consistent benefits, this research still has limitations in the number of sources and a relatively narrow study, so a broader and more in-depth follow-up study is needed.